Relationship between Physical Activity, Anthropometry, and Forced Expiratory Volume in One Second with 6-Minute Walk Distance in Elderly - Irna Purnamasari Sukarya; Vitriana Vitriana; Tertianto Prabowo (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To examine the correlation between physical activity using the Global Physical Activity Questionnaire (GPAQ), anthropometry (body mass index/BMI), and forced expiratory volume in one second (FEV1) value with six-minute walk distance in healthy community-dwelling elderly.Methods: A cross-sectional design study with consecutive sampling was conducted. This study included sixty nine participants (30 males and 39 females), aged ≥60 years who lives at Batununggal region in Bandung, Indonesia. The data was analyzed statistically by using normality, correlation, and multiple regresion tests. Results: The results showed that there was a correlation between six-minute walk distance and BMI in females (p=0.006), and FEV1 value in males (p=0.010). No significant correlation was found between GPAQ value and six-minute walk distance in females (p=0.4074) and in males (p=0.0926). Conclusions: There was a correlation between anthropometry and FEV1 value with six-minute walk distance in healthy elderly. There was no significant correlation between physical activity and six-minute walk distance. Keywords: Anthropometric measurement, FEV1, physical activity, six-minute walk distance DOI: 10.15850/ijihs.v5n1.963